2022
DOI: 10.3390/cells11061036
|View full text |Cite
|
Sign up to set email alerts
|

Predation Stress Causes Excessive Aggression in Female Mice with Partial Genetic Inactivation of Tryptophan Hydroxylase-2: Evidence for Altered Myelination-Related Processes

Abstract: The interaction between brain serotonin (5-HT) deficiency and environmental adversity may predispose females to excessive aggression. Specifically, complete inactivation of the gene encoding tryptophan hydroxylase-2 (Tph2) results in the absence of neuronal 5-HT synthesis and excessive aggressiveness in both male and female null mutant (Tph2−/−) mice. In heterozygous male mice (Tph2+/−), there is a moderate reduction in brain 5-HT levels, and when they are exposed to stress, they exhibit increased aggression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 108 publications
(159 reference statements)
0
15
0
Order By: Relevance
“…Recently, Tph2 +/− mice exposed to predator stress were shown to display excessive aggression, increased anxiety-like behaviours, and altered sociability and compromised brain metabolism of dopamine and noradrenaline [ 95 , 96 ]. The predation stress procedure elicited behavioural and molecular changes in Tph2 +/− mice that were the opposite of those observed in control mice [ 73 , 95 ]. As such, environmentally challenged Tph2 +/− mice may represent a valid model of aggression that recapitulates the role G × E interaction in the mechanisms of stress-related aggression.…”
Section: Animal Models Of Excessive Aggressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Tph2 +/− mice exposed to predator stress were shown to display excessive aggression, increased anxiety-like behaviours, and altered sociability and compromised brain metabolism of dopamine and noradrenaline [ 95 , 96 ]. The predation stress procedure elicited behavioural and molecular changes in Tph2 +/− mice that were the opposite of those observed in control mice [ 73 , 95 ]. As such, environmentally challenged Tph2 +/− mice may represent a valid model of aggression that recapitulates the role G × E interaction in the mechanisms of stress-related aggression.…”
Section: Animal Models Of Excessive Aggressionmentioning
confidence: 99%
“…Recently, in a model of stress-induced aggression in Tph2 +/− mice, we have found alterations in Plp1 and myelin basic protein (Mbp) mRNA expression in the medial PFC [ 73 ]. In this study, stressed Tph2 +/− mice with increased aggressive behaviour revealed decreased expression of these genes [ 73 ].…”
Section: Role Of Disrupted Myelination and Connectivity In Excessive ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite such a modest effect, modern neuroscientific tools keep pointing towards a serotonergic role in aggression. Since the discovery that the central nervous system has its own enzyme to synthesize serotonin (Tryptophan hydroxylase-2 (Tph-2); [ 106 ]), it was shown that a partial or complete knockdown led to more aggressive behavior in rodents [ 107 , 108 , 109 , 110 ] and could be linked to a diminished 5-HT 1A receptor sensitivity [ 111 ]. On the other hand, highly aggressive wild-derived mice had higher mRNA levels of Tph-2 than other laboratory animals [ 112 ].…”
Section: The Neurotransmission and Genetics Of Aggressionmentioning
confidence: 99%
“…We recently described a mouse model of female aggression, in which mice with partial genetic inactivation of Tph2 (heterozygous Tph2 +/− mice) were subjected to predation stress, resulting in pathological aggressive behavior (Svirin et al 2022a ) reminiscent of null mutant ( Tph2 −/− ) mice (Gutknecht et al 2012 , 2015 ). This was accompanied by abnormal expression of 5-HT receptors as well as changes in biomarkers of cellular distress, myelination and neural plasticity (Svirin et al 2022a ). However, these changes were not observed in naïve Tph2 +/− mice.…”
Section: Introductionmentioning
confidence: 99%